2022
DOI: 10.1186/s10020-022-00546-w
|View full text |Cite
|
Sign up to set email alerts
|

Targeting miR-21 in spinal cord injuries: a game-changer?

Abstract: Spinal cord injury (SCI) is a devastating neurological state causing physical disability, psychological stress and financial burden. SCI global rate is estimated between 250,000 and 500,000 individuals every year, of which 60% of victims are young, healthy males between 15 and 35 years. A variety of pathological conditions such as neuroinflammation, mitochondrial dysfunction, apoptosis, glial scar formation, blood-spinal cord barrier disruption, and angiogenesis disruption occur after SCI leading to a limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Among these miRNAs, miR-21 has been extensively investigated and has been found to possess multiple critical regulatory functions. For example, miR-21 has been shown to increase in response to spinal cord injury (SCI) and exerts various protective effects against SCI [ 11 ]. Notably, our previous study also demonstrated that the overexpressed miR-21 promoted neurite outgrowth [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these miRNAs, miR-21 has been extensively investigated and has been found to possess multiple critical regulatory functions. For example, miR-21 has been shown to increase in response to spinal cord injury (SCI) and exerts various protective effects against SCI [ 11 ]. Notably, our previous study also demonstrated that the overexpressed miR-21 promoted neurite outgrowth [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In present study, we successfully demonstrated wound healing properties of EGTE in rabbit model via gross findings, oxidative stress, connective tissue markers, pro-inflammatory markers and expression of growth markers which are considered as most important parameters for medicinal preparations having wound healing potential [ 7 , 9 , 11 ]. In recent times researchers have proposed that biomedical preparations obtained from biologics having abundant concentration of growth factors can accelerate wound healing in diabetic patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes, a metabolic disorder characterized by persistent hyperglycemia, is associated with various complications, including nephropathy, neuropathy, retinopathy, vascular dysfunction, and the development of diabetic ulcers [ [6] , [7] , [8] ]. Individuals diagnosed with diabetes face an increased risk of developing diabetic ulcers, a perplexing and highly distressing complication that further complicates their diabetes management [ 9 , 10 ]. The healthcare costs associated with treating these diabetic ulcers impose a substantial economic burden on patients, and these ulcers also exhibit a high recurrence rate, affecting approximately 50 % of diabetic individuals [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of miR-223 decreased the protein expression levels of interleukin (IL)-1β, IL-18, NLRP3, ASC, and caspase-1, and regulated the transformation of macrophages between types in injured spinal cords of mice with chronic sciatic nerve injury (Zhu et al, 2021). In addition, were involved in the apoptosis of cells after SCI (Jee et al, 2012b;He et al, 2015;Zhao et al, 2015;Xu et al, 2016;Bai et al, 2021;Huang et al, 2021;Malvandi et al, 2022;Ma et al, 2022a). miR-133b, miR-20a, and miR-124 are involved in promoting angiogenesis and regulating nerve repair after SCI (Yu et al, 2015;Theis et al, 2017;Cui et al, 2019;Wang T. et al, 2019;Danilov et al, 2020).…”
Section: The Role Of Mirnas In the Pathogenesis Of Scimentioning
confidence: 99%